Tudang Sipulung Custom In Marannu Village Maros District - Hasriani; Jumadi Sahabuddin (PT. Gudang Pustaka Cendekia, 2026)
The Tudang Sipulung tradition represents the crystallization of deliberative consensus values that persist within the agrarian communities of South Sulawesi. This study aims to describe and analyze the implementation process of the Tudang Sipulung custom in Marannu Village, Maros Regency. Employing a qualitative research method with a distinct anthropological approach, data were gathered through participant observation and in-depth interviews with key informants. The findings reveal that the execution of Tudang Sipulung in Marannu Village is not merely a ceremonial ritual but a structured forum for collective decision-making. This procession involves a synergy between traditional leaders, village government officials, agricultural extension workers, and the farming community, particularly in preparation for the rice planting season. The primary agenda includes determining planting schedules, selecting seed varieties, and managing irrigation systems to minimize the risk of crop failure. Anthropologically, this tradition serves as a medium for social integration, bridging local wisdom with technical government policies. This study concludes that the sustainability of Tudang Sipulung is a crucial factor in maintaining food security and social harmony within the Marannu Village community.